EKSPERIMENTASI MODEL PEMBELAJARAN PROBLEM SOLVING TERHADAP KEMAMPUAN PENALARAN MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR - Fitri Anggun Sari (Mat-Edukasia, 2020)
The purpose of this study is to describe the mathematical reasoning abilities in terms of learning independence using Problem Solving learning models better than conventional learning of class VIII students of SMP Negeri 43 Merangin 2018/2019 Academic Year. The research method used is experiment. The research design was a 2 x 3 factorial design. The sampling technique used was probability sampling. Data collection techniques through tests and non-tests. Based on the results of prerequisite test data analysis, it is known that the data is normally distributed and homogeneous variance. The test results show that: the mathematical reasoning ability with the Problem Solving method is better than conventional learning, the mathematical reasoning ability of high and low learning independence with the Problem Solving method is no better than conventional learning, the mathematical reasoning ability with learning independence is being moderate with the Solving method better than learning Conventionally, there is no interaction between learning models in terms of learning independence in influencing mathematical reasoning abilities